• 7 CATs FREE!
    If you earn 100 Forum Points

    Engage in the Beat The GMAT forums to earn
    100 points for $49 worth of Veritas practice GMATs FREE

    Veritas Prep
    VERITAS PRACTICE GMAT EXAMS
    Earn 10 Points Per Post
    Earn 10 Points Per Thanks
    Earn 10 Points Per Upvote
    REDEEM NOW

If \(5^x-5^{x-3}=124\cdot 5^y,\) what is y in terms of \(x?\)

This topic has expert replies
Legendary Member
Posts: 563
Joined: 01 Mar 2018
Followed by:1 members

Timer

00:00

Your Answer

A

B

C

D

E

Global Stats

If \(5^x-5^{x-3}=124\cdot 5^y,\) what is y in terms of \(x?\)

A. \(x\)
B. \(x - 6\)
C. \(x - 3\)
D. \(2x + 3\)
E. \(2x + 6\)

[spoiler]OA=C[/spoiler]

Source: GMAT Prep

Legendary Member
Posts: 1846
Joined: 02 Mar 2018
Followed by:3 members
$$5^x-5^{x-3}=124\cdot5^y$$
$$factorizing\ 5^x-5^{x-3}$$
$$5^{x-3}\cdot\left(5^3-1\right)=124\cdot5^y$$
$$5^{x-3}\cdot\left(25-1\right)=124\cdot5^y$$
$$x-3=y$$
$$y=x-3$$
$$Answer\ =\ C$$

GMAT/MBA Expert

User avatar
GMAT Instructor
Posts: 14704
Joined: 08 Dec 2008
Location: Vancouver, BC
Thanked: 5254 times
Followed by:1262 members
GMAT Score:770
Gmat_mission wrote:
Wed Jun 24, 2020 8:12 am
If \(5^x-5^{x-3}=124\cdot 5^y,\) what is y in terms of \(x?\)

A. \(x\)
B. \(x - 6\)
C. \(x - 3\)
D. \(2x + 3\)
E. \(2x + 6\)

[spoiler]OA=C[/spoiler]

Source: GMAT Prep
One option is to rewrite the left side of the equation by factoring out 5^(x-3)
So, we get: 5^(x-3)[5^3 - 1] = (124)(5^y)
Evaluate to get: 5^(x-3)[125 - 1] = (124)(5^y)
Simplify to get: 5^(x-3)[124] = (124)(5^y)
Divide both sides by 124 to get: 5^(x-3) = 5^y
So, x-3 = y

Answer: C

-----------------------------------------------------
ASIDE: A lot of students struggle to see how we can factor 5^x - 5^(x-3) to get 5^(x-3)[5^3 - 1]
Sure, they may be okay with straightforward factoring like these examples:
k^5 - k^3 = k^3(k^2 - 1)
m^19 - m^15 = m^15(m^4 - 1)
But they have problems when the exponents are variables.

IMPORTANT: Notice that, each time, the greatest common factor of both terms is the term with the smaller exponent.

So, in the expression 5^x - 5^(x-3), the term with the smaller exponent is 5^(x-3, so we can factor out 5^(x-3)

Likewise, w^x + x^(x+5) = w^x(1 + w^5)
And 2^x - 2^(x-2) = 2^(x-2)[2^2 - 1]
------------------------------------------------------------

Cheers,
Brent
Brent Hanneson - Creator of GMATPrepNow.com
If you enjoy my solutions, I think you'll like my GMAT prep course
Image
Watch these video reviews of my course
And check out these free resources

GMAT/MBA Expert

User avatar
GMAT Instructor
Posts: 14704
Joined: 08 Dec 2008
Location: Vancouver, BC
Thanked: 5254 times
Followed by:1262 members
GMAT Score:770
Gmat_mission wrote:
Wed Jun 24, 2020 8:12 am
If \(5^x-5^{x-3}=124\cdot 5^y,\) what is y in terms of \(x?\)

A. \(x\)
B. \(x - 6\)
C. \(x - 3\)
D. \(2x + 3\)
E. \(2x + 6\)

[spoiler]OA=C[/spoiler]

Source: GMAT Prep
Another option is to PLUG IN a value for x and see what kind of relationship we get between x and y.
There are two "nice" x-values to plug in. They are x = 0 and x = 3, since we can easily use these to evaluate 5^x and 5^(x-3). Of these two values, x = 3 is the easier one to plug in.
So, let's plug in x = 3
We get: 5^3 - 5^(3-3) = (124)(5^y)
Simplify to get: 125 - 1 = (124)(5^y)
Simplify to get: 124 = (124)(5^y)
Divide both sides by 124 to get: 1 = 5^y
Solve for y to get: y = 0

So, when x = 3, y = 0.

Now we'll check the answer choices to see which one satisfies this relationship.
A) y = x... So, we get 0 = 3 (NOPE)
B) y = x - 6... So, we get 0 = 3 - 6 (NOPE)
C) y = x - 3... So, we get 0 = 3 - 3 IT WORKS!
D) y = 2x + 3... So, we get 0 = 2(3) + 3 (NOPE)
E) y = 2x + 6... So, we get 0 = 2(3) + 6 (NOPE)

Answer: C

Cheers,
Brent
Brent Hanneson - Creator of GMATPrepNow.com
If you enjoy my solutions, I think you'll like my GMAT prep course
Image
Watch these video reviews of my course
And check out these free resources

GMAT/MBA Expert

User avatar
GMAT Instructor
Posts: 5170
Joined: 25 Apr 2015
Location: Los Angeles, CA
Thanked: 43 times
Followed by:23 members
Gmat_mission wrote:
Wed Jun 24, 2020 8:12 am
If \(5^x-5^{x-3}=124\cdot 5^y,\) what is y in terms of \(x?\)

A. \(x\)
B. \(x - 6\)
C. \(x - 3\)
D. \(2x + 3\)
E. \(2x + 6\)

[spoiler]OA=C[/spoiler]

Solution:

We can simplify the given equation:

5^x – 5^(x- 3) = 124*5^y

5^x – (5^x)(5^- 3) = 124*5^y

5^x(1 – (5^- 3)) = 124*5^y

5^x(1 – 1/125) = 124*5^y

5^x(1 – 1/125) = 124*5^y

5^x(124/125) = 124*5^y

5^x = 124*5^y*(125/124)

5^x = 5^y(125)

5^x = 5^y(5^3)

5^x = 5^y+3

x = y + 3

x - 3 = y

Answer: C

Scott Woodbury-Stewart
Founder and CEO
scott@targettestprep.com

Image

See why Target Test Prep is rated 5 out of 5 stars on BEAT the GMAT. Read our reviews

ImageImage